Comparison of Nitroglycerine VS Nifedipine for Preterm Labour (Medical Forum Monthly, 2024)
Objective: The objective of this study is to compare outcome of Nitroglycerine versus Nifedipine to delay the time of preterm delivery.Study Design: Randomized controlled trial study.Place and Duration of Study: This study was conducted at the Obstetrics and Gynaecology Department, Hayatabad Medical Complex, Peshawar, from July, 2016 to January, 2017.Materials and Methods: This study was carried out over 154 women with preterm delivery who were divided into two groups equally through lottery method. One group, group A, was subjected to treatment with Nifedipine and the other group, group B, to nitroglycerine. After informed consent, all the females were followed until the delivery of baby and the complications were noted in predesigned Performa. The subjects were selected through non-probability purposive sampling. Entry and analysis of the data was done in SPSS (version 10).Results: A total of 154 patients were observed, who were divided in two equal groups. Average age was 29.58 years ±7.75SD with range of 16-42 years. In group A, out of 77 patients, there was 1 day prolongation of pregnancy in 18 (23.4%),in 42 (54.5%) there was 2 days prolongation of pregnancy followed by 17(22.1%)in whom pregnancy was prolonged for more than 2 days. While in-group B in 19(24.7%) there was 1 day prolongation of pregnancy,in 46(59.7%)there was 2 days prolongation of pregnancy followed by 12(15.6%) patients in whom pregnancy was prolonged for more than 2 days. Although the difference in prolongation of pregnancy in both the groups was insignificant with p-value 0.585 but it was prolonged in Group A. Post-treatment headache occurred to 15(19.5%) patients in group A and to 20(26%)patients in group B, however it did not reach statistical significance with p- value 0.336. Of the neonates born to mothers in group A 15(19.5%) were admitted in NICU while in group B 25(32.5%) were admitted in NICU with p-value 0.066.Conclusion: Nifedipine is better treatment as compared to Nitroglycerine for preterm delivery.